The Role of Situational Leadership and Organizational Culture in Efforts to Improve Digital Literacy (A Case Study of Widuri Junior High School, Kebon Jeruk Subdistrict, West Jakarta) - Anggita Muliani; Ersam Mahendrawan; Lili Nurlaili (Riviera Publishing, 2026)
The rapid development of ICT has elevated digital literacy as a critical competency in education. SMP Widuri Jaya, an A-accredited private junior high school in Kebon Jeruk, West Jakarta, faces challenges in digital literacy among its educators. The objective aims to examine the role of situational leadership and organizational culture in enhancing digital literacy among educators at SMP Widuri Jaya. A qualitative case study design was employed. Five informants were selected purposively: the principal, vice-principal for student affairs, head of laboratory and library, ICT teacher, and homeroom teacher. Data were collected through in-depth interviews, direct observation, and documentation, then analyzed using open, axial, and selective coding. Validity was ensured through source and technique triangulation. The results situational leadership is at a moderate level, characterized by adaptive but informal leadership styles with task delegation primarily directed toward full-time and homeroom teachers. Organizational culture also operates at a moderate level, marked by limited formal digital policies and mild innovation. Five integrated dimensions emerged: human resource competency, organizational communication and collaboration, member empowerment, organizational culture and work values, and organizational stability and conflict management. Supporting factors include Wi-Fi infrastructure, personal devices, training, leadership support, and reward systems. Inhibiting factors encompass unequal digital competencies, dependence on specific individuals, absent formal policies, incomplete library digitalization, and low educator motivation. Both situational leadership and organizational culture significantly contribute to digital literacy enhancement; systematic formal policy development and competency-based empowerment strategies are urgently needed.